Činčilinči, Grundž - Slobodová, Elena; Klimo, Alojz, 1922-2000 (Bratislava : Mladé letá, 1987)
Detské ľudové hry a vyčítanky.
Keywords: slovenská literatúra; ľudové hry detské; vyčítanky; predškolský vek